Предмет: Алгебра,
автор: anuta1250
Помогите пожалуйста, заранее спасибо!
Решите уравнение:
x(x-2)(x+1)=х^2(х-1)
(^2-во второй степени)
Ответы
Автор ответа:
0
x(x-2)(x+1)=x^2(x-1)
x(x^2+x-2x-2)=x^3-x^2
x^3+x^2-2x^2-2x=x^3-x^2 (переносим)
x^3+x^2-2x^2-2x-x^3+x^2=0 (сокращаем)
-2x=0
x=0
Проверяем:
0(0-2)(0+1)=0^2(x-1)
0=0
x(x^2+x-2x-2)=x^3-x^2
x^3+x^2-2x^2-2x=x^3-x^2 (переносим)
x^3+x^2-2x^2-2x-x^3+x^2=0 (сокращаем)
-2x=0
x=0
Проверяем:
0(0-2)(0+1)=0^2(x-1)
0=0
Похожие вопросы
Предмет: Английский язык,
автор: anelgalymova
Предмет: Математика,
автор: michurov2000
Предмет: Химия,
автор: balimbek85
Предмет: Информатика,
автор: Программистка5
Предмет: История,
автор: irasharova1